PENGARUH MEDIA BUKU ENSIKLOPEDIA IPTEK UNTUK MENINGKATKAN LITERASI MEMBACA SISWA BERBANTUAN MODEL AKTUALISASI KEPRAMUKAAN DI SD NEGERI CIKONENG - Priatna, Asep; Syifa Hermawati Putri; Acep Roni Hamdani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
Indonesia is ranked 60th out of 61 countries in terms of reading interest according to the results of the World's Most Literate Nations Ranked research conducted by John W. Miller on 16 March 2016. Based on observation and research with the fifth grade teacher of SD Negeri Cikoneng, students find it difficult to learn literacy because they have to read slowly, lack of interest in books other than Thematic, and lack of motivation. The study aims to determine the application, effect, and improvement of Science and Technology Encyclopedia Book in improving Students' Reading Literacy assisted by Scouting Actualisation Model at SD Negeri Cikoneng. The research was conducted through a quantitative approach using the Quasi-Experiment method and the type of non-equivalent control group design with the object of research being grade V students in the 2022/2023 school year of SD Negeri Cikoneng. The research population was 25 male students and 31 female students and the research sample was 26 class A students as an experimental class with 12 boys and 14 girls and 30 class B students as a control class with 13 boys and 17 girls. The results showed that in the application of Science and Technology Encyclopedia Book Media to improve Student Reading Literacy assisted by the Scouting Actualisation Model at Cikoneng State Elementary School, students were able to read science and technology encyclopedia books. This is evidenced by the Mann Whitney U test score of 0.195. The results showed that there was an effect of science and technology encyclopedia book to improve students' reading literacy assisted by the Scouting Actualisation Model. This is evidenced by the results of the Mann Whitney U test score of 0.195. Then the results showed a moderate increase in students' reading literacy towards the Science and Technology Encyclopedia Book assisted by the Scouting Actualisation Model. This is evidenced by the N-Gain test of 0.62342440 or 62% increase in the experimental class and the Effect Size test resulted in a value of 0.244044919 which is in the medium category. Overall, it can be concluded that there is a positive influence in the use of the Science and Technology Encyclopedia Book assisted by the Scouting Actualisation Model on increasing student reading literacy. Through the Science and Technology Encyclopedia Book, students can apply and deepen their understanding of the material studied and is an effective approach to improving student reading literacy at SD Negeri Cikoneng.